Clinical Profile and Treatment Outcome of Endogenous Endophthalmitis (KYAMC Journal, 2024)
Background: Endogenous Endophthalmitis is a sight threatening intraocular infection resulting from hematogenous spread of pathogens from distant foci.Objective: To find out the source, risk factors, microbiological profile, visual and anatomical outcome of management of Endogenous endophthalmitis.Materials and Methods: A retrospective study was done from medical records of diagnosed case of Endogenous Endophthalmitis at Vision Eye Hospital, Dhaka. Data collection was done on demographic factors, medical and surgical history, infectious data, BCVA throughout the clinical course and complications. Visual outcome and anatomical outcome were measured and compared.Results: 20 Eyes of 18 patients were diagnosed as Endogenous Endophthalmitis where 88.9% were unilateral and 11.1% were bilateral. Known foci of infection were found in 27.8% of cases and infective foci were not found on 33.3%. 44.4% were culture positive where the commonest organism was Pseudomonas followed by Klebsiella. 70% patients were treated by PPV and 30% were treated conservatively. Among 18 patients 6 had normal eyeball, 7 had formed eyeball, 3 developed phthisis bulbi and 1 needed enucleation. Finally, VA improved at 44.4% patients, remain unchanged at 22.2% patients and deteriorated at 33.3% patients. Conclusion: The prognosis of endogenous endophthalmitis is often poor despite treatment. A high index of suspicion, early diagnosis and prompt treatment are crucial to salvage vision and eye.KYAMC Journal Volume: 14, No: 04, January 2024: 220-225.